brain litz 1 world history updated edition - Lorenzo, J. Ramon S.; J. Ramon S. Lorenzo (Philippines National Bookstore, 1984)
Television quiz champion Ramon Lorenzo had painstakingly searched far and wide to give you the Brain Blitz and IQ booster series of reviewers.
English